Genotype and phenotype relationships in 10 Pakistani unrelated patients with inherited factor VII deficiency. (4th June 2013) - Borhany, M.; Boijout, H.; Pellequer, J.‐L.; Shamsi, T.; Moulis, G.; Aguilar‐Martinez, P.; Schved, J.‐F.; Giansily‐Blaizot, M.
Summary: Inherited factor VII (FVII) deficiency is one of the commonest rare bleeding disorders. It is characterized by a wide molecular and clinical heterogeneity and an autosomal recessive pattern of inheritance. Factor VII‐deficient patients are still scarcely explored in Pakistan although rare bleeding disorders became quite common as a result of traditional consanguineous marriages. The aim of the study was to give a first insight of F7 gene mutations in Pakistani population. Ten unrelated FVII‐deficient patients living in Pakistan were investigated (median FVII:C = 2%; range = 2–37%). A clinical questionnaire was filled out for each patient and direct sequencing was performed on the coding regions, intron/exon boundaries and 5′ and 3′ untranslated regions of the F7 gene. Nine different mutations (eight missense mutations and one located within the F7 promoter) were identified on the F7 gene. Five of them were novel (p.Cys82Tyr, p.Cys322Ser, p.Leu357Phe, p.Thr410Ala, c‐57C>T, the last being predicted to alter the binding site of transcription factor HNF‐4). Half of the patients had single mutations in Cys residues involved in disulfide bridges. The p.Cys82Arg mutation was the most frequent in our series. Six of seven patients with FVII:C levels below 10% were homozygous in connection with the high percentage of consanguinity in our series. In addition, we graded the 10 patients according to three previously published classifications for rare bleeding disorders. The use of the bleeding score proposed by Tosetto and co‐workers in 2006 appears to well qualify the bleeding tendency in our series.